(untitled) (Journal of Enam Medical College, 2021)
Efferent loop obstruction is a very rare post-gastrectomy obstruction that can occur following Billroth-II or Roux-en-Y reconstruction. Here we report a case who underwent gastrojejunostomy for gastric outlet obstruction 30 years back and now developed efferent loop obstruction due to phytobezoar. The efferent loop obstruction was successfully resolved by laparotomy. J Enam Med Col 2020; 10(2): 118-121